Tula orthohantavirus nucleocapsid protein is cleaved in infected cells and may sequester activated caspase-3 during persistent infection to suppress apoptosis. (3rd July 2019) - Davies, Katherine; Afrough, Babak; Mankouri, Jamel; Hewson, Roger; Edwards, Thomas A.; Barr, John N.
Abstract : The family Hantaviridae mostly comprises rodent-borne segmented negative-sense RNA viruses, many of which are capable of causing devastating disease in humans. In contrast, hantavirus infection of rodent hosts results in a persistent and inapparent infection through their ability to evade immune detection and inhibit apoptosis. In this study, we used Tula hantavirus (TULV) to investigate the interplay between viral and host apoptotic responses during early, peak and persistent phases of virus infection in cell culture. Examination of early-phase TULV infection revealed that infected cells were refractory to apoptosis, as evidenced by the complete lack of cleaved caspase-3 (casp-3C) staining, whereas in non-infected bystander cells casp-3C was highly abundant. Interestingly, at later time points, casp-3C was abundant in infected cells, but the cells remained viable and able to continue shedding infectious virus, and together these observations were suggestive of a TULV-associated apoptotic block. To investigate this block, we viewed TULV-infected cells using laser scanning confocal and wide-field deconvolution microscopy, which revealed that TULV nucleocapsid protein (NP) colocalized with, and sequestered, casp-3C within cytoplasmic ultrastructures. Consistent with casp-3C colocalization, we showed for the first time that TULV NP was cleaved in cells and that TULV NP and casp-3C could be co-immunoprecipitated, suggesting that this interaction was stable and thus unlikely to be solely confined to NP binding as a substrate to the casp-3C active site. To account for these findings, we propose a novel mechanism by which TULV NP inhibits apoptosis by spatially sequestering casp-3C from its downstream apoptotic targets within the cytosol.